The Judge's Consideration on The Case of Rejection of The Lawsuit Related to Land Grabbing (Study of Decision No. 189/PDT. G/2020/PN PLK) - Febrizha, Meishy; Hayati, Mulida; Martono, Yacob F (Law Development Journal, 2025)
Land disputes in Indonesia are still a complex and recurring legal issue, especially in cases of land grabbing that involve the act of controlling or using another party's land without legitimate rights. This problem often leads to judicial proceedings because it is related to property rights protected by the Basic Agrarian Law. However, many lawsuits were rejected because the plaintiff could not prove land ownership or did not meet the formal or material requirements as stipulated by the civil procedure law. This study aims to analyze the judge's consideration in rejecting the land grabbing lawsuit in Decision No. 189/PDT. G/2020/PN PLK and identify the legal variables that affect the decision. The method used is qualitative research with a normative juridical approach through literature study. The results of the study showed that the judge rejected the lawsuit by referring to Article 1365 of the Civil Code regarding unlawful acts and Article 1865 of the Civil Code regarding the principle of the burden of proof. The plaintiff was considered incapable of fulfilling the elements of unlawful acts and failed to present authentic evidence, such as land deeds and certificates, as the basis for ownership rights in accordance with the UUPA.